2016
DOI: 10.3390/molecules21010094
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis, Optimization of Extraction Conditions and Biological Evaluation of Corylopsis coreana Uyeki Flos

Abstract: Abstract:A method for the separation and quantification of three flavonoids and one isocoumarin by reverse-phase high performance liquid chromatography (HPLC) has been developed and validated. Four constituents present in a crude ethanolic extract of the flowers of Coryloposis coreana Uyeki, were analyzed. Bergenin, quercetin, quercitrin and isosalipurposide were used as calibration standards. In the present study, an excellent linearity was obtained with an r 2 higher than 0.999. The chromatographic peaks sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 36 publications
1
57
0
3
Order By: Relevance
“…In our previous study, 80% ethanolic extract showed optimal 2,2diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, reducing power and phenolic content. [10] Thus, based on the results of our previous study and the findings of the current study, the 80% ethanolic extract was selected for further in-vitro and in-vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, 80% ethanolic extract showed optimal 2,2diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, reducing power and phenolic content. [10] Thus, based on the results of our previous study and the findings of the current study, the 80% ethanolic extract was selected for further in-vitro and in-vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that BER, ISO, QCT and QCIT are the main bioactive phytochemicals identified from C. coreana Uyeki flos. [10] Thus, these four constituents were analysed in the 80% ethanolic extract that was prepared in this study. BER was one of the major compounds in the 80% ethanolic extract of C. coreana Uyeki flos.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations